Invasive Meningococcal Disease in the Vaccine Era - Nadel, Simon; Ninis, Nelly (Frontiers in Pediatrics, 2018)
Infection with the bacterium Neisseria meningitidis (the meningococcus) is one of the main causes of meningitis and septicemia globally. Humans are the only reservoir for the meningococcus, which resides primarily in the nasopharynx; colonization occurs in approximately 10% of adults and may be found in up to a quarter of individuals during adolescence. Prompt recognition of meningococcal infection and aggressive early treatment are vital in reducing mortality, which occurs in approximately 10% of those with invasive meningococcal disease (IMD), even with treatment, and can be significantly higher in those with inadequate or delayed treatment. The rapid and timely recognition of IMD is of critical importance to improving patient survival and outcomes. Prompt administration of effective parenteral antimicrobial therapy and early recognition and management of the complications of IMD, including shock and raised intracranial pressure (ICP), are critical to improving patient outcomes. This review will summarise the clinical features of IMD and current treatment recommendations. We will also discuss the evidence for immunization and effects of vaccine strategies, particularly the implementation of vaccination against Group B meningococcus.